Lupin as a Source of Bioactive Antioxidant Compounds for Food Products - Lorenzo Estivi; Andrea Brandolini; Andrea Gasparini; Alyssa Hidalgo (Molecules, 2023)
Four species of lupin (white lupin, yellow lupin, blue lupin and Andean lupin) are widely cropped thanks to the excellent nutritional composition of their seeds: high protein content (28–48 g/100 g); good lipid content (4.6–13.5 g/100 g, but up to 20.0 g/100 g in Andean lupin), especially unsaturated triacylglycerols; and richness in antioxidant compounds like carotenoids, tocols and phenolics. Particularly relevant is the amount of free phenolics, highly bioaccessible in the small intestine. However, the typical bitter and toxic alkaloids must be eliminated before lupin consumption, hindering its diffusion and affecting its nutritional value. This review summarises the results of recent research in lupin composition for the above-mentioned three classes of antioxidant compounds, both in non-debittered and debittered seeds. Additionally, the influence of technological processes to further increase their nutritional value as well as the effects of food manufacturing on antioxidant content were scrutinised. Lupin has been demonstrated to be an outstanding raw material source, superior to most crops and suitable for manufacturing foods with good antioxidant and nutritional properties. The bioaccessibility of lupin antioxidants after digestion of ready-to-eat products still emerges as a dearth in current research.